2020
DOI: 10.1016/j.aohep.2020.08.062
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 another kind of liver aggressor, how does it do that?

Abstract: Clinical manifestations of SARS-CoV-2 infection include more frequently fever and cough, but complications (such as pneumonia, respiratory distress syndrome, and multiorgan failure) can occur in persons with additional comorbidities. Liver dysfunction is one of the most striking affections among patients suggesting that SARS-CoV-2 may represent a new king of liver aggressor. However, the molecular process underlying this phenomenon is still unclear. In this work, we overview the most recent findings between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 57 publications
0
31
0
4
Order By: Relevance
“…Higher incidence of acute cardiac injury was reported [ 113 ] HBV Body fluid Yes Increased liver tissue damage and inflammatory responses due to COVID-19 may aid HBV co-infection by overexpressing host cell receptors [ 114 ]. It may also fuel the reactivation of pre-existing chronic HBV [ 115 ]. Elevation of ALT, AST, TBIL, ALP, and γ-GT.…”
Section: Molecular Mechanism Of Co-infection In Covid-19mentioning
confidence: 99%
“…Higher incidence of acute cardiac injury was reported [ 113 ] HBV Body fluid Yes Increased liver tissue damage and inflammatory responses due to COVID-19 may aid HBV co-infection by overexpressing host cell receptors [ 114 ]. It may also fuel the reactivation of pre-existing chronic HBV [ 115 ]. Elevation of ALT, AST, TBIL, ALP, and γ-GT.…”
Section: Molecular Mechanism Of Co-infection In Covid-19mentioning
confidence: 99%
“… 12 There have also been reports of coronavirus particles in hepatocytes without a defined mechanism for infection. 13 …”
Section: Introductionmentioning
confidence: 99%
“…12 There have also been reports of coronavirus particles in hepatocytes without a defined mechanism for infection. 13 In a recent report studying the receptome of spike binding, ACE-2 was confirmed as the primary receptor for the spike protein via the binding domain (RBD) on the spike 1 portion of the molecule and the N-terminaldomain as the sites critical for virus-host interaction. 14 Additionally, the report described binding of the spike protein with ectopically expressed ASGR1 and KREMEN1 in transfected non-liver cells.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 was first reported (2). Besides the respiratory system, entry receptor angiotensin-converting enzyme 2 (ACE2) receptors are also expressed in cholangiocytes, allowing SARS-CoV-2 to enter and replicate in the liver (3). There are case reports of liver-related serious adverse outcomes among patients with COVID-19 (4), and observational studies have reported that SARS-CoV-2 can result in abnormal liver enzymes in patients with HBV (5).…”
mentioning
confidence: 99%